Impact of Internet Addiction Upon Educational Performance of Students Nursing Secondary Schools in Baghdad City (Medico Legal Update, 2020)
The study aimed to assess Impact of internet addiction upon educational performance of Students nursingSecondary schools in Baghdad city. A descriptive - analytic study used the assessment approach from 10September 2017 to 30 November 2017 in order to study the impact of internet addiction upon educationalperformance of Students nursing Secondary schools was conducted in Baghdad city. Non probability(purposive) sample is selected for the study which includes (100) students .Data were gathered through thepatients interviewed. Assessment questionnaire consist of two parts contains demographic characteristic,theother part concerning about assessment of internet addict. The validity and reliability of the instrumentwas determined by using through the panel of experts, and internal consistency through the computation ofAlpha Correlation Coefficient. The data have been collected through the utilization of the interview. Datawere analyzed through the application of descriptive statistical (frequencies and percentages).and inferentialanalysis chi by applying the Statistical Package for Social Science version 21.0(SPSS).The finding of thestudy showed that the highest percentage is located within the age group of twenties (46.8%) (130%) theof the sample was female and represents 84.8% aged 20-29 years. distribution of participants within thelevels of Body Image Disorder and distributes as 29.9% having extremely severe level. 32.4% with faceprocedures have very high and high levels of self-esteem. The study concluded that Clients seeking cosmeticSurgery have moderate and severe level ofBody Image and psychological DistressResearcher recommended the first consultation should be with the psychiatric physician before cosmeticsurgery done.